Geovisualising 3D cultural heritage building for urban tourism via mobile augmented reality application / Fedeline Lowenda Roginal ... [et al.] - Roginal, Fedeline Lowenda; Abdul Rasam, Abdul Rauf; Ghazali, Rosmadi; Jaafar, Saiful Anuar (Faculty of Information Management, 2023)
Augmented Reality (AR) is a virtualization technology, contributing to visual contents without completely replacing the user's field of view. Tourists can visit interesting areas and explore their surroundings while AR technology that displays information and material relevant to them. Combining these two elements can enhance travel experiences and provide more information about particular locations and features. The study aims to develop a mobile AR apps of a 3D urban heritage building at Sarawak Cultural Village. The first objective of this study has been achieved by conducting a survey on the user requirement of the proposed AR app, and the findings revealed that the local communities need the apps for urban cultural tourism destinations. The second objective is to design and develop the apps using SketchUp, Unity 3D, and Vuforia, and the result show that it could offer several special features and functions of a practical system for visualising the 3D cultural heritage building in Sarawak. While the last objective has proved that this proposed AR apps are developed with aligned to the user requirements and system testing for the local tourism and heritage departments.